Impact of Recent Migration and Local Income Disparity: Does Time Variying Imply? - Fajri, Moh Najikhul; Istifadah, Nurul; Munawaroh, Siti; Pratama, Backtiar Putra (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2023)
Temporary migration is one part of the potential for income inequality in the region. On this basis, this study aims to examine the effect of temporary migration on income disparity. This study uses SUSENAS panel data from 34 provinces during 2010-2019. This study uses the generalized method of moments dynamic panel regression to analyze the time change while reviewing the regional aspect. The results show that in-migration has a significant positive effect on income disparity. Meanwhile, out-migration has a negative effect on income disparity. Moreover, inflation and consumption expenditure are suspected to cause the severity of inequality. On the other hand, average years of schooling encourage people to get good labor productivity. This upward migration policy implies that it is an alternative for regions to reduce income inequality. The policy is navigated from various transmissions such as education, investment, access to public services, central and local coordination, and monitoring of labor exploitation practices.